Diseño de un sistema de dosificación volumétrica para jabón en polvo (2017)
It was identified that the small companies that market toilet products are in the objective of finding advances in the technification of the filling process that is being carried out manually. Since in the cleaning products the filling process must be carried out exactly with the quantity and weight determined in each one of them. Already diagnosed the current situation of the process, it was proposed and evaluated design alternatives for this machine thanks to the information found in design books, theses and websites. Subsequently, we proceeded to select the most appropriate alternative for this type of process.